2011
DOI: 10.1093/jxb/err146
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel α-L-arabinofuranosidase gene associated with mealiness in apple

Abstract: In order to investigate the genetic bases of the physiological syndrome mealiness that causes abnormal fruit softening and juice loss in apples, an integrative approach was devised, consisting of sensory, instrumental, biochemical, genetic, and genomic methods. High levels of activity of α-L-arabinofuranosidase (α-AFase), a hydrolase acting on the pectic component of the cell walls, were found in individuals exhibiting the mealiness phenotype in a segregating population. The expression levels of the previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…Arabinose is one of the major sugar component of pectic rhamnogalacturonan-I side chains that have been shown in vitro to form hydrogen bond with cellulose (Zykwinska et al, 2005). Furthermore, arabinofuranosidase activity and arabinofuranosidase gene MdAF3 expression were positively correlated with apple mealiness (Nobile et al, 2011). All these data suggest that the putative bonds of pectic arabinan side chains to cellulose and their regulation by enzymes may play a critical role on cell wall mechanical properties and fruit texture.…”
Section: Correlations Between Chemical Measurements and Mechanical Pamentioning
confidence: 86%
“…Arabinose is one of the major sugar component of pectic rhamnogalacturonan-I side chains that have been shown in vitro to form hydrogen bond with cellulose (Zykwinska et al, 2005). Furthermore, arabinofuranosidase activity and arabinofuranosidase gene MdAF3 expression were positively correlated with apple mealiness (Nobile et al, 2011). All these data suggest that the putative bonds of pectic arabinan side chains to cellulose and their regulation by enzymes may play a critical role on cell wall mechanical properties and fruit texture.…”
Section: Correlations Between Chemical Measurements and Mechanical Pamentioning
confidence: 86%
“…Nobile et al (2011) reported that the gene expression and enzyme activity of α- l -arabinofuranosidase (α-AFase), acting on the pectic component of the cell wall, were correlated with mealiness. By transcriptome analysis, the expression of a pectin methylesterase gene ( MdPME2 ) was found to be significantly higher in non-mealy fruits than in mealy fruits during fruit development, ripening, and post-harvest (Segonne et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…5 Due to ripening and senescence after harvest, kiwifruit quality will be seriously affected, and the storage period will be shortened because of membrane deterioration, cell-wall degradation, cell-structure modification, and cell death. 6 Cell-wall degradation is associated with cell-wall hydrolases, including pectinesterase (PME), 7 polygalacturonase (PG), 8,9 ⊎-gal, 10 ⊍-arabinofuranosidase (⊍-L-af), 11,12 xyloglucan endotransglycosylase / hydrolase (XTH), 13,14 and cellulase. 15 Pectinesterase catalyzes the demethylesterification of cell-wall polygalacturonans, 16 which promotes the hydrolysis of polygalacturonic acid by PG.…”
Section: Introductionmentioning
confidence: 99%